(untitled) (Homoeopathy for All, 2024)
Background: A food allergy is an unfavorable reaction with an immunological basis that develops after exposure to a particular food on a regular basis. When the immune system is unable to develop or maintain oral tolerance to specific dietary proteins, food allergies develop. Objectives: To study the effectiveness of homoeopathic management in food allergies. Methods: An Observational Prospective Study which is conducted at Alva’s Homoeopathic medical college and Hospital, Mangalore during the year 2022- 2023. 30 patients were selected based on purposive sampling based on inclusion and exclusion criteria. Erlangen symptom score was taken as assessment scale in which all symptoms of the patients were collected before and after the treatment. Dr. J.T. Kent’s repertorization was used to calculate totality. The improvement following therapy was evaluated using a paired t test based on the assessment scale. Results: All sorts of food allergies can be treated safely, gently, and effectively with homoeopathy’s symptomatological approach. After treatment, this study’s use of the Erlangen symptom score revealed a considerable change. After receiving symptomatic homoeopathic treatment, the patient improved. Conclusion: It is determined that the homoeopathic symptomatological method is highly efficient in treating food allergies.